Respuesta :

Answer:

[tex]13-12x[/tex]

Step-by-step explanation:

[tex]3-4x(2+1)+10[/tex]

Add 2 and 1 to get 3.

[tex]3-4x*3+10[/tex]

Multiply 4 and 3 to get 12.

[tex]3-12x+10[/tex]

Add 3 and 10 to get 13.

[tex]13 - 12x[/tex]

Answer:

13

Step-by-step explanation:

let’s start with the parentheses because of PEMDAS.

2+1 = 3

Before we can do multiplication we need to subtract 3 from 4.

3-4 = 1

Now we can multiply 1 by 3.

1x3 = 3

Next we add.

3+10= 13

And there’s your answer.

ACCESS MORE